Medical Cannabis Brand Architecture: Establishing its Roots in Pharmaceutical Marketing - Ntais, Christos; Suvatjis, Jean; Melanthiou, Yioula (My University, 2023)
Purpose: This paper investigates how cannabis can be introduced through brand architecture as a medicinal product. It discusses the setting of medical cannabis brand architecture and classifies cannabis products into brands under a brand hierarchy. Design/Methodology/Approach: A literature review produced a pool of data related to medical cannabis and brand architecture and set the foundation for devising a medical cannabis brand architecture pattern for administrative brand manageability and applicability. Findings: According to the literature review, a number of issues related to medical cannabis, branding, brand architecture and marketing were evaluated and considered. After considering all the components of traditional (generic) marketing theory, we proceed with a Customer Analytic Approach (PCA2) to enable us to construct and adopt an appropriate brand architecture model (the Triadic model) which would be aligned with medical cannabis holistic marketing strategy and future product line. Practical implications: The analysis of the devised brand architecture strategy considered a number of issues such as the nature of the product, potential customers, its intended use and its current stigmatization status and resulted in a proposed commercialization process. Originality/value: The examination of current brand issues, customer idiosyncrasies, purchasing intentions and market opportunities were considered in order to accurately and insightfully construct a brand architecture for cannabis as a future medicinal product, benefiting not only the firms selling it but society in general with respect to its pharmacological properties.
Keywords: brand architecture; branding; marketing; Medical cannabis